SPOILAGE OF SPOTTED SEER(SCOMBEROMOROUS GUTTATUS) DURING ICE STORAGE. - SHENOY, A VASANTH (Fishery Technology, 2017)
Quality deterioration of seer h.eld directly in contact withice, in different forms, fillets and chunks, and of chunks heldin ice but without direct contact, was studied for a period of15 days. While the chunks held out of contact with ice wereacceptable upto 13 days based on organoleptic evaluations, thechunks and fillets held in direct contact with ice were acceptableonly upto 10 days. The order of preference of the samplesat any interval of ice storage was chunks held out of contactwith ice> chunks held directly in ice> fillets held directly in ice.The changes in the chemical quality of these samples were alsoin the same order, the deterioration being maximum in filletsand least in chunks kept out of contact with ice.